2020
DOI: 10.1136/rmdopen-2020-001395
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of tofacitinib up to 9.5 years: a comprehensive integrated analysis of the rheumatoid arthritis clinical development programme

Abstract: ObjectiveTofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). We report the largest integrated safety analysis of tofacitinib, as of March 2017, using data from phase I, II, III, IIIb/IV and long-term extension studies in adult patients with RA.MethodsData were pooled for patients with RA who received ≥1 tofacitinib dose. Incidence rates (IRs; patients with events/100 patient-years [PY]; 95% CIs) of first-time occurrences were obtained for adverse events (AEs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
118
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 68 publications
14
118
2
12
Order By: Relevance
“…The safety profile of tofacitinib in RA has been mainly characterized in extensive RCTs, LTE studies (ORAL SEQUEL up to 9.5 years), and the phase IV Oral Surveillance trial [ 11 ]. The summary of safety results from studies in the tofacitinib clinical development program is shown in Table 1 .…”
Section: Overall Safety Profilementioning
confidence: 99%
See 4 more Smart Citations
“…The safety profile of tofacitinib in RA has been mainly characterized in extensive RCTs, LTE studies (ORAL SEQUEL up to 9.5 years), and the phase IV Oral Surveillance trial [ 11 ]. The summary of safety results from studies in the tofacitinib clinical development program is shown in Table 1 .…”
Section: Overall Safety Profilementioning
confidence: 99%
“…HZ and pneumonia were the infections that most frequently led to the discontinuation of the treatment. Cohen et al [ 11 ], in an ISS of 9.5 years of experience with tofacitinib and 7061 patients (22,875 PYs of exposure), described an incidence rate (IR) for SAEs of 9.0 [95% confidence interval, (CI): 8.6–9.4]. Wollenhaupt et al [ 12 ], in a LTE study of up to 9.5 years of experience, showed that 52% of patients (from a total of 4481) discontinued the treatment with tofacitinib, 24% due to AEs and 4% because of inadequate response.…”
Section: Overall Safety Profilementioning
confidence: 99%
See 3 more Smart Citations